Aquisiç\~ao de terras por estrangeiros no Brasil: Uma avaliaç\~ao jurídica e econômica - Fábio Augusto Santana Hage; Marcus Peixoto; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The rise in agricultural prices to alarming levels since 2007 characterized the agrinflation phenomenon. Because of the increase in food prices and the expectation of strong population growth in the coming years, the issue of land grabbing by foreigners in the world has been drawing the attention, especially in African and Latin American regions. In Brazil, the land grabbing by foreigners has increased since 2008. In 2010, this increase has led the General Attorney of the Union (AGU) to reinterpret the Brazilian legislation of land acquisition, in order to limit the access to Brazilian landed property by foreigners. The debate about land grabbing by foreigners is controversial. There is no doubt about the importance of monitoring the integration of foreigners in Brazilian economy, which can be done by registering and updating data from land acquisition data. Moreover, there should be caution in terms of investments from sovereign wealth funds from countries with strong interest in importing Brazilian primary products. However, it is important to mention that the state can regulate the market even with a legislation that is more flexible to foreign investments.
Keywords: Q15; Q18; R52; 330; agriculture; legislation; land grabbing